2008
DOI: 10.1007/s10653-008-9200-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Santa Catarina (Brazil) coal with respect to human health and environmental concerns

Abstract: The current paper presents the concentration, distribution, and modes of occurrence of trace elements of 13 coals from south Brazil. The samples were collected in the state of Santa Catarina. Chemical analyses and the high ash yields indicate that all studied coals are rich in mineral matter, with SiO(2) and Al(2)O(3) dominating as determined by inductively coupled plasma-atomic emission spectrometry (ICP-AES). Quartz is the main mineral species and is associated with minor levels of feldspars, kaolinite, hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 22 publications
1
28
0
1
Order By: Relevance
“…Brazilian coals have considerable concentrations of pyrite (Silva et al 2009b), which has recently been shown to spontaneously generate hydrogen peroxide (H 2 O 2 ) (Cohn et al 2005) and hydroxyl radicals ( • OH) (Cohn et al 2004) when placed in water. The formation of these reactive oxygen species (ROS) also explains the recent observation that aqueous pyrite slurries degrade yeast RNA, ribosomal RNA and DNA (Cohn et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Brazilian coals have considerable concentrations of pyrite (Silva et al 2009b), which has recently been shown to spontaneously generate hydrogen peroxide (H 2 O 2 ) (Cohn et al 2005) and hydroxyl radicals ( • OH) (Cohn et al 2004) when placed in water. The formation of these reactive oxygen species (ROS) also explains the recent observation that aqueous pyrite slurries degrade yeast RNA, ribosomal RNA and DNA (Cohn et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…These power plants produce approximately 3 Mt of ash per year, of which 65-85% is fly ash and 15-35% bottom ash. In Santa Catarina, where the largest of the thermal plants is located, the coals used for power production tend to be high in ash and sulfur (Silva et al, 2009a). There is also considerable concern over particulate matter, due to the low efficiency of fine-particle-emissions control systems (Teixeira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained on trace elements in our samples are shown in Table 1. Because of the lower calorific value, combustion by-products from Brazilian coals can be expected to have larger amounts of non-volatile elements per unit of energy than U.S. coals, but the concentrations of these elements in the Brazilian combustion byproducts are diluted by the high quartz contents (Silva et al 2009b). …”
Section: Resultsmentioning
confidence: 99%
“…Various trace elements, such as As, Co, Cu, Pb, Ni, Se, uranium (U), and Zn, are concentrated in coal (Table 1) and are harmful to the health of aquatic and Silva et al (2009b) terrestrial organisms (US Environmental Protection Agency 2002a, b). These were also found in the CMD water samples collected in this study (Table 2).…”
Section: Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation